Evaluasi Program Salat Duha Berjamaah dengan Pendekatan CIPP di SMPIT Darul Fikri Makassar - K, Khaerunnisa; S, Syamsudduha (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to evaluate the duha prayer program at SMPIT Darul Fikri Makassar using the CIPP (Context, Input, Process, Product) evaluation model with descriptive evaluative qualitative methods. Data were collected through interviews and observations of coaches, institutions, and students. The results showed that the duha prayer program is effective in increasing the spiritual value, religious character, discipline, and responsibility of students in carrying out sunnah worship. The implementation of duha prayer is carried out routinely, supervised by class coaches, and is part of the Shahihul Ibadah assessment in the school report card. The context evaluation shows that the program is designed to get learners used to performing sunnah worship consistently. The input evaluation identified the support of coaches' competence, adequate facilities and relevant curriculum. The process evaluation revealed structured implementation, congregation on school days, and independent in the boarding rooms on weekends. The product evaluation highlighted the program's success in creating togetherness, increasing spiritual awareness and shaping learners' noble morals. However, challenges such as the individual motivation of learners to carry out worship with full awareness still need to be improved. By strengthening the role of coaches and supporting facilities, this program is expected to continue to make a positive contribution in shaping a religious, disciplined and responsible generation.